Adjuvant systemic therapy in early breast cancer and results of a prospective observational multicenter BRIDE study: patients outcome and adherence to guidelines in cancer clinical practice - Gori, Stefania; Fabi, Alessandra; Angiolini, Catia; Turazza, Monica; Salvini, Piermario; Ferretti, Gianluigi; Cretella, Elisabetta; Gianni, Lorenzo; Bighin, Claudia; Toss, Angela; Zamagni, Claudio; Vici, Patrizia; et al. (Frontiers in Oncology, 2025)
IntroductionEvaluation of every breast cancer (BC) patient by multidisciplinary team and application of guidelines are very important to ensure the best treatment and achieve the best outcome.MethodsThe multicenter prospective observational BRIDE study enrolled, from 01/2018 to 02/2021, 1633 BC patients from 19 Italian cancer centers. To evaluate the clinical and biopathological characteristics of BC patients with pathological stage I-II-III treated with surgery followed by adjuvant systemic therapy, type of therapies delivered, outcome and adherence to guidelines, an analysis of 1123 patients out of 1633 patients enrolled in BRIDE study was conducted.ResultsThe 1123 patients with stage I-II-III BC had a median age of 61.2 years (Q1-Q3: 50.6-71.7); 70.2% were postmenopausal, 92.1% had ECOG PS 0, 68.4% pT1 disease, 70.7% pN0, 91.7% pathological stage I-II; 68.9% underwent conservative breast surgery and 79.8% sentinel lymph node biopsy alone. According to phenotypic subgroup, 80.6% of patients had a HER2-negative/HR-positive, 10.4% HER2-positive/HR-positive, 6.4% triple negative and 2.6% HER2-positive/HR-negative BC. In clinical practice, the phenotypic tumoral subgroup influenced oncologists in the choice of the type of adjuvant systemic therapy (p<0.0001) according to ESMO and AIOM Guidelines. Adjuvant radiotherapy was administered to 85.5% patients undergoing breast-conserving surgery. At the median follow up of 41.4 months (Q1: 35.3 months – Q3: 57.9 months), the DFS at 48 months was 92.8%, with different rates in the phenotypic subgroups. The adherence to AIOM Guidelines in clinical practice was ≥ 70% for the four evaluated quality indicators of treatment process.DiscussionIn patients with pathological stage I-II-III BC, the phenotypic subgroup influenced the oncologists’ decision on the choice of type of adjuvant systemic therapy, as also indicated by international and national guidelines. In our patients, the DFS rate at 24 and 48 months after surgery was 95.4% and 92.8% respectively. The adherence to the AIOM Guidelines in clinical practice was high but having both quality indicators (shared at international and national level) to evaluate the quality of care in BC and standardized threshold levels to evaluate adherence to guidelines is very important today because this type of evaluation will increase in the coming years.